2014
DOI: 10.1007/s11103-014-0271-0
|View full text |Cite
|
Sign up to set email alerts
|

Cucumber ECERIFERUM1 (CsCER1), which influences the cuticle properties and drought tolerance of cucumber, plays a key role in VLC alkanes biosynthesis

Abstract: Most land plants have a wax layer which covers their aerial parts to protect them from environmental stresses, such as drought, UV radiation, and pathogenic invasion. The wax biosynthesis has been well studied previously in Arabidopsis, but it still remains elusive in cucumber. Here, we isolated a CER1 homolog CsCER1 in cucumber, and we found that the expression of CsCER1 in the cucumber line 3401 which shows waxy fruit phenotype is much higher than that in the cucumber line 3413 which displays glossy fruit ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
92
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 117 publications
(102 citation statements)
references
References 50 publications
10
92
0
Order By: Relevance
“…These results are similar to experiments where the Arabidopsis CER1 was overexpressed in the Arabidopsis wild type, also prompting drastic increases in alkanes (Bourdenx et al, 2011). Conversely, a wheat loss-of-function mutant, the nullisomic-tetrasomic substitution line, showed reduced alkane amounts, again similar to the cer1 mutant phenotypes of other species (Aarts et al, 1995;Wang, Zhang, Xu, Ren, et al, 2015).…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…These results are similar to experiments where the Arabidopsis CER1 was overexpressed in the Arabidopsis wild type, also prompting drastic increases in alkanes (Bourdenx et al, 2011). Conversely, a wheat loss-of-function mutant, the nullisomic-tetrasomic substitution line, showed reduced alkane amounts, again similar to the cer1 mutant phenotypes of other species (Aarts et al, 1995;Wang, Zhang, Xu, Ren, et al, 2015).…”
Section: Discussionsupporting
confidence: 81%
“…These findings parallel previous reports where overexpression of the homologous Arabidopsis CER1 gene resulted in increased relative water content after water deprivation, higher biomass accumulation, and, thus, enhanced drought resistance. Similar effects were also observed for rice and cucumber CER1 homologs (Wang, Zhang, Xu, Ren, et al, ; Zhou et al, ). Overall, our results confirmed that TaCER1‐1A, like CER1s in other species, plays an important role in reducing plant surface permeability and, hence, contributes to drought tolerance.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…In many cases, overexpression of these TFs negatively affects plant growth and yield [93,97]. Recently, Wang et al [98] isolated a CER1 homolog CsCER1, a gene involved in alkane biosynthesis, in cucumber. They showed that abnormal expression of CsCER1 in transgenic cucumber plants had strong effects on very-long-chain (VLC) alkane biosynthesis, cuticle permeability and drought resistance.…”
Section: Controlling Water Loss Through the Cuticlementioning
confidence: 99%
“…Cucumber ( Cucumis sativus ; 2n = 2x = 14) is an economically important vegetable crop cultivated around the world (Huang et al ., ; Li et al ., ; Yang et al ., ). The cucumber fruit is a pepo that is covered with tubercules, trichomes and a thick cuticle (Roth, ; Wang et al., ). Usually, the larger trichomes on cucumber fruits are called spines and are composed of a stalk and a base (Chen et al ., ).…”
Section: Introductionmentioning
confidence: 99%